Dialectic between Digital Culture and Islamic Business Ethics in Online Business: A Literature Review - Suad Fikriawan; Khafidhoh; Teguh Ansori (MONETARIUM: Journal of Economics Business and Management, 2026)
This study aims to analyze the relationship between digital culture and the implementation of Islamic business ethics in Muslim online businesses. The development of digital technology has driven significant transformations in business practices, particularly through the utilization of e-commerce and social media as the main platforms for transactions and marketing. However, various ethical challenges related to honesty, transparency, and responsibility in digital business activities have emerged. This study employs a qualitative method with a literature analysis technique for various relevant scholarly sources. The review findings show that digital culture shapes new behavior patterns in Muslim online businesses, but the implementation of Islamic business ethics remains suboptimal and tends to be partial. Gaps in digital ethics literacy, the dominance of profit orientation, and the lack of integration of Sharia principles in digital systems are the main factors hampering the consistent application of ethics. In addition, digital culture also has the potential to commodify religious values in business practices. Therefore, a more systematic integration between digital culture and Islamic business ethics is required through the strengthening of value literacy, the internalization of ethics, as well as the development of regulations and sharia-based technology, in order to create a sustainable and just digital business ecosystem